Effects and pregnancy outcomes of L‐carnitine supplementation in culture media for human embryo development from in vitro fertilization - Kim, Min Kyoung; Park, Jae Kyun; Paek, Soo Kyung; Kim, Ji Won; Kwak, In Pyung; Lee, Hee Jun; Lyu, Sang Woo; Lee, Woo Sik (The journal of obstetrics and gynaecology research, 2018)
Aim Antioxidants have been studied to be effective in improving embryo qualities from in vitro fertilization. L‐carnitine (LC) has been known to reduce reactive oxygen species and enhance adenosine triphosphate production, which contribute to the development of a high‐quality embryo. This is the first study to include both mouse and human subjects and aimed to evaluate whether LC supplementation in culture media has any beneficial effect on the development of the embryos, as well as its clinical outcomes. Methods Mouse embryos were used as models in the animal studies for cell immunofluorescent staining evaluation. Inner cell mass and trophectoderm (TE) cells were counted and statistically analyzed between LC and control groups. For human studies, medical records of patients with infertility undergoing in vitro fertilization procedures from January to May 2017 were included and the embryos were divided into two groups at the two pronuclear stage. Statistical analysis was performed to compare the embryo status and clinical outcomes of the two groups. Results In the animal study, the LC group showed significantly higher numbers of cells in the inner cell mass and trophectoderm, indicating better development. In the human studies, there were significantly higher numbers of good‐quality embryos on days 2, 3 and 5 in the LC group than in the control. The clinical outcomes, such as implantation, clinical pregnancy and ongoing pregnancy rates, were also higher in the LC group than in the control. Conclusion LC supplementation in culture media improved human embryo quality and eventually achieved better pregnancy outcomes.